Efficiency and effectiveness of implicit and explicit approaches for the analysis of shape-memory alloy bodies. (February 2016) - Scalet, Giulia; Auricchio, Ferdinando; Hartl, Darren J
The increasing number of applications incorporating shape-memory alloy (SMA) components motivates the development of three-dimensional constitutive models to enhance their analysis and design. These models only reach their full utility if they are then implemented into numerical (e.g. often finite-element-based) frameworks. The present article addresses a topic rarely considered in the myriad of SMA computational analysis works in the literature: the analysis of the time and accuracy of implementation options. In particular, this work proposes to compare the performance of the implicit and explicit integration methods for two common three-dimensional phenomenological constitutive models: (i) the model by Lagoudas et al.; and (ii) the model by Auricchio et al. available in all installations of Abaqus. In doing so, the present work develops and implements an explicit algorithm for the model by Lagoudas et al. for the first time. The investigated models are compared in a chosen benchmark boundary value problem analysis considering both thermally induced actuation and isothermal stress-induced transformation of an SMA beam. The performance of the methods in terms of analysis time and parallelization efficiency are also investigated.